Good governance and strong institutions in achieving sustainability for the benefit of society - Mohd Israil, Khaliq Ahmad; Khaliq, Zaid; Musa, Adam; Ssemuddu, Imran (World Academy of Islamic Management, 2026)
The practices of cronyism generate considerable unrest and inequity, undermining societal stability, a phenomenon often linked to mismanagement and inadequate or poor governance. This research examined the contributions of the Madani government in diminishing the Malaysian Corruption Index by implementing effective governance for its populace, hypothesising that by 2028, it will rank among the 25 least corrupt nations. Consequently, this study aimed to assess the statutory agents mandated to combat corruption in Malaysia on behalf of the Madani government. The degree of corruption exhibited a notable change from 2022 to 2025. A thorough examination of the Transparency International databases spanning from 2015 to 2024 was conducted to produce descriptive statistics aimed at assessing the present scale of initiatives undertaken by the MACC (Malaysian Anti-Corruption Commission) and NACS (National Anti-Corruption Strategy) in combating corruption in Malaysia. Analysing the nation with the lowest score in juxtaposition with the highest-ranked CPI. Evaluating in relation to SDG 16 and its associated global indicators, the findings have been presented in tabular form. The results demonstrate that the statutory institutions tasked with combating corruption on behalf of the Madani government have consistently attained three points in their role since the present government assumed leadership of Malaysia. In summation, the Madani administration and its anti-corruption operatives must enhance their efforts to meet the self-imposed benchmark of 10 points by the year 2028